A Qualitative Study of Female Migrant Domestic Workers’ Experiences of and Responses to Work-Based Sexual Violence in Cyprus - Kouta, Christiana; Pithara, Christalla; Apostolidou, Zoe; Zobnina, Anna; Christodoulou, Josie; Papadakaki, Maria; Chliaoutakis, Joannes (My University, 2021)
Domestic workers face increased risk for sexual harassment and assault in the workplace but are often reluctant to disclose abuse or seek retribution. We report on a study looking at mi grant domestic workers’ responses to sexual violence, reasons behind their responses, and factors enhancing or diminishing vulnerability to abuse. We carried out qualitative, in-depth, individual and group interviews with 15 female domestic workers from the Philippines and Sri Lanka working in the Republic of Cyprus. Descriptive thematic analysis was used to analyse data using QSR NVivo 10.0. Sexual violence against migrant domestic workers was reported to be rampant, particularly among women living with their employer. Perpetrators took advantage of women’s precarious legal, social, and economic circumstances to coerce women into a sexual relationship. All participants reported taking action to stop attacks despite the significant barriers they faced: racism and discrimi nation, social isolation, and hostile legal, labour, and immigration systems. Fear of losing their job, being deported, and facing racism and discrimination from the police were the biggest barriers to seeking retribution. Access to informational, e.g., legal, practical, and emotional support, facilitated positive outcomes following abuse, such as finding a new employer. Systemic racism, hostile labour and immigration systems, and lack of support increase risk of sexual violence and place barriers against accessing safe working spaces, protection, and justice. Women need to be informed of the risks involved in domestic work and empowered to identify abuse and access help and support when needed.
Keywords: Migrant women; Domestic work; Sexual harrassment; Sexual violence; Empowerment